Phenotypic Plasticity in Sexual Reproduction Based on Nutrients Supplied From Vegetative Ramets in a Leymus chinensis Population - Guo, Jian; Li, Haiyan; Yang, Yunfei (Frontiers in Plant Science, 2020)
Phenotypic plasticity is considered a major mechanism that allows plants to adapt to heterogeneous environments. The physiological integration between the interconnected rhizomes or stolons of clonal plants influences the plasticity of such plants in heterogeneous environments. However, the determinants of plasticity of reproductive ramets in clonal plants in homogeneous environments are unclear. Here, we chose Leymus chinensis, a perennial rhizomatous grass, and conducted a series of field experiments in situ, including grading sampling of reproductive ramets and different connection forms of vegetative ramets labeled with 15N at four reproductive stages. Reproductive ramet biomass, inflorescence biomass, seed number, seed-setting percentage, reproductive allocation and reallocation significantly increased with an increase in the number of vegetative ramets connected to tillering nodes, and the plasticity indexes of these six phenotypic characteristics showed similar increasing trends. The amount of nutrients supplied from the connected vegetative ramets to the reproductive ramets was significantly affected by the transfer direction, reproductive stage, and position order of the vegetative ramets. Throughout the sexual reproduction stage, nutrients were preferentially transferred to the acropetal reproductive ramet in L. chinensis populations. The amount of nutrients supplied from the connected vegetative ramets to the reproductive ramets at the milk-ripe stage, when sexual reproduction was most vigorous, was significantly larger than that at other reproductive stages. The amount of nutrients supplied from the spacer vegetative ramet to the acropetal reproductive ramet was significantly larger than that to the basipetal reproductive ramet. The closer the vegetative ramet was to the reproductive ramet, the more nutrients were supplied; the amount of nutrients supplied was significantly negatively related to the position order of the vegetative ramet. We identified the determinant of plasticity in sexual reproduction in clonal plants in a homogeneous environment: physiological integration between ramets within clones. Our results are vital for better understanding the adaptation of populations and even the evolution of species of clonal plants.